Implementation and approbation of the convergent model of professional foreign language competence in university conditions - Tleuzhanova, G.K.; Assanova, D.N.; Dzholdanova, D.K. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article discusses the theoretical and practical aspects of implementing a convergent model of professional foreign language competence into the educational process at a university, which involves integrating informal education into the institutional educational environment. Based on current research, the authors justify the use of a convergent approach to foreign language training for future specialists as a means of creating a flexible and adaptive educational system that combines the best aspects of both learning formats. The key components of the model were presented, its testing methods were outlined, and the results of its implementation were analyzed. The significance of using the convergent approach to develop foreign language competence in students was substantiated. The aim of this article is to present the results of implementing and testing the convergent model of professional foreign language competence at a university, as well as to analyze its effectiveness. To achieve this goal, the following tasks were formulated: 1) to describe the theoretical foundations of the convergent approach in foreign language teaching; 2) to present a model of professional foreign language competence based on the convergence of various methods; 3) to test the model and assess its effectiveness. As a result of the study, the conclusion was made that the implementation of the convergent model of professional foreign language competence at the university contributes to more effective language acquisition, increased student motivation, and the integration of various methods into the educational process.
Жоо-да кәсіби шеттілдік құзыреттіліктің конвергенттік моделін енгізу және сынақтан өткізу
Внедрение и апробация конвергентной модели профессиональнойиноязычной компетенции в условиях вуза
Keywords: convergence; professional foreign language competence; convergent model; pedagogical innovations; formal education; informal education; informal foreign language education